Investigating the Behavioral Pattern of Stock Market Index and Covid-19 Crisis: Case Study G20 Stock Market Indices - Agbortoko, Egbe Agbortoko (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
This research focuses on investigating the behavioral patterns of stock market indices during the Covid-19 period, with the time period under assessment ranging from January 2015 to September 2022. The principal aim and objective of the research is to assess the volatility spillover of various stock market indices, with further derivations of both net transmitters and receivers of the volatility spillovers in the financial market. The principal econometric method used is the Diebold and Yilmaz approach (2012). The results show a high rate of interconnectedness between the stock market indices in the financial market. The analysis reveals that the volatility in the market during the outbreak of the pandemic is due to its outburst, given that its total spillover index estimates are about 51%, and all observed series demonstrate stationarity at the level state I(0). These results emphasize the importance of information circulation in financial markets, as rational investment decisions by current and potential investors are backed by information adequacy. Additionally, the results demonstrate the relevance of health as an important factor in deriving the proficiency levels of stock market indices, with further illustrative evidence of a non-trading period as a result of the pandemic outbreak.

ÖZ: Bu araştırma, Ocak 2015'ten Eylül 2022'ye kadar değişen değerlendirme dönemi ile Covid-19 döneminde borsa endekslerinin davranış modellerini incelemeye odaklanmaktadır. Araştırmanın temel amacı, çeşitli hisse senetlerinin oynaklık yayılımını değerlendirmektir. Kullanılan başlıca ekonometrik yöntem Diebold ve Yılmaz yaklaşımıdır (2012). Sonuçlar, finansal piyasada borsa endeksleri arasında yüksek oranda karşılıklı bağlantı olduğunu göstermektedir. Analiz, toplam yayılma endeksi tahminlerinin yaklaşık %51 olduğu ve gözlemlenen tüm serilerin I(0) seviye durumunda durağanlık gösterdiği göz önüne alındığında, pandeminin patlak vermesi sırasında piyasadaki dalgalanmanın salgının patlamasından kaynaklandığını ortaya koyuyor. Mevcut ve potansiyel yatırımcıların rasyonel yatırım kararları bilgi yeterliliği ile desteklendiğinden, bu sonuçlar finansal piyasalarda bilgi dolaşımının önemini vurgulamaktadır. Ek olarak, sonuçlar, pandemi salgınının bir sonucu olarak ticaret yapılmayan bir döneme ilişkin daha fazla açıklayıcı kanıtla birlikte, borsa endekslerinin yeterlilik düzeylerinin elde edilmesinde sağlığın önemli bir faktör olarak önemini göstermektedir.
Master of Science in Banking and Finance. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2023. Supervisor: Assist. Prof. Dr. Nigar Taşpınar.
Keywords: Thesis Tez; Banking and Finance Department; Stock Exchange--Stock Market--COVID-19 Pandemic, 2020-; Volatility spillovers; stock market indices; Covid-19